2021
DOI: 10.1177/20458940211001714
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pulmonary vasodilator use in Veterans with pulmonary hypertension associated with left heart disease and lung disease

Abstract: Randomized trials of pulmonary vasodilators in pulmonary hypertension (PH) due to left heart disease (Group 2) and lung disease (Group 3) have demonstrated potential for harm. Yet these therapies are commonly used in practice. Little is known of the effects of treatment outside of clinical trials. We aimed to establish outcomes of vasodilator treatment for Groups 2/3 PH in real-world practice. We conducted a retrospective cohort study of 132,552 Medicare-eligible Veterans with incident Groups 2/3 PH between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…A comprehensive study of data from 132 552 veterans with PH diagnosed in groups 2 and 3 found a 39% increased mortality or organ failure in those exposed to pulmonary vasodilators (HR, 1.31 [95% CI, 1.25–1.37]). 141…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…A comprehensive study of data from 132 552 veterans with PH diagnosed in groups 2 and 3 found a 39% increased mortality or organ failure in those exposed to pulmonary vasodilators (HR, 1.31 [95% CI, 1.25–1.37]). 141…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…50 Algorithms that are multicomponent and include the presence of PAH medications, diagnostic codes, and procedural codes improve performance. 50,52,53 The development and validation of algorithms outside of Group 1 PH are especially challenging in part because therapies approved for the treatment of PAH are used on and off-label for the treatment of other PH groups (e.g., PH in interstitial lung disease, chronic thromboembolic pulmonary hypertension [CTEPH]). Compounded with the lack of specificity in diagnostic codes, researchers are limited in their ability to discriminate patients within the five clinical classification groups in claims data.…”
Section: Current Status Of Rwd In Ph and Opportunities For Improvemen...mentioning
confidence: 99%
“…3 Worldwide, PH Group 2 is thought to affect 5%-10% of elderly individuals (>65 years), 3 and indepth analyzes reveal that PH Group 3 encompasses another very large group of PH, far outnumbering Group 1 patients. 4 Global epidemiological data indicate that approximately 20% of all hospitalized patients might present with some variant of PH or pulmonary pressure elevation. 5 Taken together, these findings support the contention that PH is substantially more prevalent than commonly assumed and constitutes a comorbidity of global significance.…”
Section: Introductionmentioning
confidence: 99%
“…Usually considered a rare disease, due to the historical focus on idiopathic PAH (IPAH), current estimates calculate an age‐dependent PH prevalence of about 1% of the global population, which increases up to 10% in the elderly 3 . Worldwide, PH Group 2 is thought to affect 5%–10% of elderly individuals (>65 years), 3 and in‐depth analyzes reveal that PH Group 3 encompasses another very large group of PH, far outnumbering Group 1 patients 4 . Global epidemiological data indicate that approximately 20% of all hospitalized patients might present with some variant of PH or pulmonary pressure elevation 5 .…”
Section: Introductionmentioning
confidence: 99%